Titulación de predios por prescripción adquisitiva de dominio, política incluyente para el acceso efectivo a la vivienda digna en la comunidad de la localidad de Rafael Uribe Uribe. (2021)
Informal housing in Colombia is an invisible problem and is addressed as one more issue among the different topics on the country's agenda. Due to its imprecise nature and the lack of information about its origin, it becomes a phenomenon that is difficult to measure, however, as it is related to poverty and the socio-demographic conditions of the population, it is an issue of great importance for everyone. For this reason, in this work an evaluation of the legal parameters that support the inclusion of comprehensive degree projects within public policies is carried out, in order to generate an improvement in the quality of life of the people of the Town of Rafael Uribe Uribe. For the development of this work, initially, possible solutions to the problem of illegal land occupation were analyzed in accordance with those established in the Rafael Uribe Uribe Locality Development Plan.